International medical graduates' experiences of clinical competency assessment in postgraduate and licensing examinations: A scoping review protocol. - Helen Hynes; Anél Wiese; Nora McCarthy; Catherine Sweeney; Tony Foley; Deirdre Bennett (PLoS ONE)
An international medical graduate (IMG) is a doctor who has received their basic medical qualification from a medical school located in a different country from that in which they practice or intend to practice. IMGs are known to face difficulties in their working lives, including differential attainment in assessment. The objective of this review is to map key concepts and types of evidence in academic and gray literature relating to international medical graduates' experiences of clinical competency assessment and to identify knowledge gaps on this topic by systematically searching, selecting, and synthesizing existing knowledge. All studies will relate to IMGs. The concept of interest will be IMGs' experiences of assessment. The context will be postgraduate, licensing or credentialing medical assessments of clinical competence. This review will be conducted in accordance with the Joanna Briggs Institute (JBI) methodology for scoping reviews. Seven electronic databases will be searched for literature published between 2009 and 2024: the Australian Education Index, British Education Index, ERIC, PubMed, PsycINFO, Scopus, and SocINDEX. Gray literature will be searched using Google, Google Scholar, and published reports from postgraduate training bodies and medical licensing organizations. Documents will be independently screened, selected, and extracted by two researchers using a piloted data-extraction tool. Data will be analyzed and presented in tables and in a narrative format. Trial resgistration: Scoping review registration: Open Science Framework: https://osf.io/8gdm7.